ANALISIS KESALAHAN BERBAHASA BERITA PADA WEBSITE RESMI DINAS PENDIDIKAN KOTA SURABAYA - Faiz Abdul Malik, Mochammad; Catur Budiyono, Sunu (Universitas PGRI Adi Buana Surabaya, 2019)
Surabaya Education Office’s Official Website is directly managed by IT staff of SurabayaEducation Office’s. As a government institution under the Ministry of Education and Culture,it is proper that this agency implements a good and correct language. No exception to thelanguage of journalistic variety used in the official website. Therefore, the official website ofthe Surabaya City Education Office should apply the Indonesian spelling in accordance withPermendikbud Number 50 of 2015 on General Spellings Guidelines of Bahasa Indonesiaaccompanied by the Fourth Edition of the Fourth Edition of the Indonesian Spelling Manual(PUEBI). However, the fact is still found many errors related spelling and sentences that arenot effective on the official website of the Office of Education. Above this background, thisresearch was made with the purpose of describing and analyzing the error language on theofficial website of Surabaya Education Department. In this study, the data will be examined interms of the spelling according to the General Spellings Guidelines of Indonesia. In addition,it is also noted in terms of the effectiveness of sentences because this is an important thing inthe news. News must convey information in its entirety, and to convey information as a wholerequires effective sentences. This research uses qualitative approach. The data studied are tennews that aired in August 2017 on the official website of Surabaya City Education Department.To collect the data, the author visited http://dispendik.surabaya.go.id. Data were collected bydocumentation technique. After the data is collected, it will then be analyzed and described forthe errors encountered. In this study found errors in terms of spelling and ineffectiveness ofsentences. Related spelling errors, including writing punctuation, capitalization writing,oblique writing, number writing, and word writing. Not only that, the ineffectiveness ofsentences is also found in the data collected.